Keep it up : the power of precision medicine to conquer low T and revitalize your life - Comite, Florence (Rodale, 2013)
"'Men in their 40s and 50s aren't feeling right,' says New York endocrinologist Florence Comite, MD. 'They're foggy, like they've lost their edge, yet mainstream medicine has no answers for them." Dr. Comite's answer is to help men regain the vitality of their 20s today using a protocol of medical therapies that she says won't become mainstream for another 20 years. Comite's futuristic approach is controversial, as a New York Times Magazine article on her practice described last year. But more physicians are beginning to accept the idea that midlife malaise has a real (and treatable) physiological basis known as andropause. In her sure-to-be talked about book, Dr. Comite argues that the proper response is to do a deep dive into a man's health history and biological makeup through special tests and then to tweak the his hormones through diet, exercise, key nutrients and medications. The goal: to return a man to the strength, mental clarity and sexual vitality he experienced in his 20s. It's a new science of maintaining youth that any man can tap with the help of his doctor to ensure a strong, healthy, and active second half of life"--